Aplikasi Sel Surya untuk Penerangan Warga di Pulau Balang Caddi Kabupaten Pangkajene dan Kepulauan - Azwar Hayat; Onny Sutreasman; Ahmad Yusran Aminy; Andi Erwin Eka Putra; Lukmanul Hakim Arma; Hairul Arsyad; Novriany Amaliyah; Gerard Antonini Duma; Asriadi Sakka; Rudi Rudi (Faculty of Engineering UNHAS, 2022)
Balang Caddi Island is one of the islands in the Pangkajene dan Kepulauan Regency where most of the people work as fishermen. Administratively the island is Mattiro Bintang Subdistrict, Liukang Tuppabiring District. The island is a remote area that often receives less attention. The electrical energy crisis experienced by the people of this island needs to address as soon as possible. With this community service, we are implementing new renewable energy solar cells for lighting residents on Balang Caddi Island. This Solar Cell application will be placed in one of the residents house as a pilot project for the application of new and renewable energy. The community will also receive training on how to maintain the tool so that the community will independently maintain the sustainability of the program in the future. A 100 wp Solar Cell with a 216 Wh battery is installed to power 2 pieces of 7 watt lamps, 2 pieces of 9 watt lamps, 30 watt fan and 50 watt TV. The lamp is operated at night for 6 hours with a total power consumption of 192 watts. Fans and TVs are operated during the daytime only by utilizing direct solar energy converted from the DC current of the solar cell to the AC current using a 300 watt inverter. On a daily basis, benefits are obtained in the form of free electricity of 300-400 watts per day to meet the needs of the residents of Balang Caddi island. This activity have succeeded in transforming the residents Balang Caddi island. This can be seen from the results of the Pre-test and Post-test which showed an increase in knowledge from really don't know 26.4% to very knowledgeable 83.3%, an increase in skills from really don't know 87.5% to very capable 94.6% and an increase in attitude from really don't know 20% to really know 100%.